Signaling pathways and targeted therapy for rosacea - Yang, Fengjuan; Wang, Lian; Song, Deyu; Zhang, Lu; Wang, Xiaoyun; Du, Dan; Jiang, Xian (Frontiers in Immunology, 2024)
Rosacea is a chronic skin inflammatory disease with a global prevalence ranging from 1% to 20%. It is characterized by facial erythema, telangiectasia, papules, pustules, and ocular manifestations. Its pathogenesis involves a complex interplay of genetic, environmental, immune, microbial, and neurovascular factors. Recent studies have advanced our understanding of its molecular basis, focusing on toll-like receptor (TLR) 2 pathways, LL37 expression, mammalian target of rapamycin (mTOR) activation, interleukin (IL)-17 signaling, transient receptor potential vanilloid (TRPV) functions, and the Janus kinase-signal transducer and activator of transcription (JAK-STAT) pathways. LL37-associated signaling pathways, particularly involving TLR2 and mTORC1, are critical in the pathogenesis of rosacea. LL37 interacts with signaling molecules such as extracellular signal-regulated kinases 1 and 2 (ERK1/2), nuclear factor kappa B (NF-κB), inflammasomes, C-X-C motif chemokine ligand 8 (CXCL8), mas-related G-protein-coupled receptor X2 (MRGPRX2)-TRPV4, and vascular endothelial growth factor (VEGF). This interaction activates macrophages, neutrophils, mast cells, and vascular endothelial cells, leading to cytokine release including tumor necrosis factor-alpha (TNF-α), IL-6, IL-1β, C motif chemokine ligand (CCL) 5, CXCL9, and CXCL10. These processes contribute to immune response modulation, inflammation, and angiogenesis in rosacea pathophysiology. The IL-17 signaling pathway also plays a crucial role in rosacea, affecting angiogenesis and the production of inflammatory cytokines. In addition, recent insights into the JAK/STAT pathways have revealed their integral role in inflammatory and angiogenic mechanisms associated with rosacea. Rosacea treatment currently focuses on symptom management, with emerging insights into these molecular pathways providing more targeted and effective therapies. Biological agents targeting specific cytokines, IL-17 inhibitors, JAK inhibitors, and VEGF antagonists are promising for future rosacea therapy, aiming for enhanced efficacy and fewer side effects. This review provides a comprehensive overview of the current knowledge regarding signaling pathways in rosacea and potential targeted therapeutic strategies.